An Analysis of Presuppositions in the Selected Song Lyrics of Hendry Moodie’s Album - Simanjuntak, Fransisca; Hasibuan, Wan Syahfina Yahmi; Manurung, Lastri W; Manik, Sondang (Journal of Applied Linguistics, 2025)
This study analyzed the presuppositions in the song lyrics of Hendry Moodie’s album to uncover deeper meanings and emotional nuances in his music. The research focused on five selected songs: "Drunk Text," "Orbit," "Pick Up the Phone," "You Were There for Me," and "Closure." Using qualitative content analysis, presuppositions were categorized based on Levinson’s and Yule’s frameworks, including existential, factive, lexical, structural, non-factive, and counterfactual types. The analysis revealed the distribution of presupposition types as follows: "Drunk Text" (15% existential, 20% factive, 20% lexical, 20% structural, 10% non-factive, 15% counterfactual), "Orbit" (20% existential, 20% factive, 20% lexical, 20% structural, 10% non-factive, 10% counterfactual), "Pick Up the Phone" (20% existential, 20% factive, 20% lexical, 20% structural, 10% non-factive, 10% counterfactual), "You Were There for Me" (20% existential, 20% factive, 20% lexical, 20% structural, 10% non-factive, 10% counterfactual), and "Closure" (15% existential, 20% factive, 20% lexical, 20% structural, 10% non-factive, 15% counterfactual). The findings indicated that Moodie’s use of presuppositions enriched the depth of his lyrics, guiding listeners toward specific interpretations and emotional responses. By embedding implicit assumptions, Moodie enhanced the narrative and emotional resonance of his songs, fostering a deeper connection with his audience. This research contributed to a better understanding of how linguistic devices in song lyrics influence listener perception and engagement. It provided new insights into the relationship between language and emotion in music, demonstrating the power of presupposition in shaping the emotional impact of lyrics. Keywords : Presupposition; song lyrics; Hendry Moodie; linguistic analysis